Patellofemoral Arthroplasty: Short-Term Complications and Risk Factors - Rezzadeh, Kevin; Behery, Omar A.; Kester, Benjamin S.; Dogra, Tara; Vigdorchik, Jonathon; Schwarzkopf, Ran (The Journal of Knee Surgery, 2019)
There is a paucity of literature regarding the short-term readmission, reoperation, and complication rates of patellofemoral arthroplasty (PFA). The purpose of this study is to determine the incidence and risk factors of 30-day postoperative complications in patients undergoing PFA. A retrospective cohort study of subjects who underwent PFA from 2010 to 2015 was performed using the American College of Surgeons National Surgical Quality Improvement Program (NSQIP) database. Perioperative outcomes and 30-day postoperative complications were ascertained, and patient demographics and comorbidities were analyzed using linear and binomial logistic regression analyses to determine risk factors for postoperative complications. Among the 1,069 patients identified in the NSQIP database, there was a 30-day readmission rate of 4.3% and a 30-day reoperation rate of 1.5%. The leading complications identified were bleeding requiring transfusion (11.7%), urinary tract infection (0.8%), and deep vein thrombosis (DVT) (0.8%). Younger age was a risk factor for superficial wound infection (p = 0.012). Older age was a significant risk factor for longer hospital stays, readmission, bleeding requiring transfusion, urinary tract infection, and pneumonia (p < 0.05 for all). Male sex was a risk factor for longer operation time and DVT (p = 0.001 and p = 0.017, respectively), while female sex was associated with greater incidence of bleeding requiring transfusion (p = 0.049). Elevated body mass index (BMI) was a risk factor for longer hospital stays, greater total operation time, and bleeding requiring transfusion (p < 0.001, p < 0.001, and p = 0.001, respectively). Nonwhite race was a significant risk factor for readmission (p = 0.008). This represents the largest study on early readmissions and the associated risk factors after PFA. PFA 30-day readmission and reoperation rates were <5%. Older age and elevated BMI were both identified as risk factors for adverse perioperative outcomes, including longer operation times, longer hospital stays, and bleeding requiring transfusion.
Keywords: patellofemoral arthroplasty; 30-day complication; patellofemoral joint arthritis; risk factors; NSQIP